Strategic Management in the Knowledge Economy - A. D. Vorobyov (Управленческие науки, 2018)
Subject. The subject of the study is the methodology of a unified approach to the model of strategic management under the conditions of the knowledge economy.Purpose. To show the possibility of integrating various modern approaches into the theory and methodology of strategic management in the knowledge management model.Methodology. The methodology of the unified approach is based on I. Ansoff’s views on the strategic actions outlined by the author in the work “The New Corporate Strategy”. The main provisions of the knowledge economy are borrowed from the founders of this trend: Grant R., Nonaka L., SengeP., TecceD. and others.Results. The unified model is characterized by: a unified scheme for strategic analysis, the overall strategic tools, strategic model of development system. At the same time, the work of the knowledge management model (the humanist) is based on a combination of two subsystems: education and the “soft” control. The first one plays the role of a site where there is a process of working with ideas, suggestions of staff for strategic development of the organization. The soft management creates a creative atmosphere and is governed by the synergetic regularities and tools. The latter are sufficiently simply described in strategic terms and categories. The integration of the strategic model and the knowledge management model is achieved by evolutionary way from the simple economic model of strategic behavior to the strategic planning model, then to the transitional conglomerative model and, finally, to the innovative strategic model of organizational and management content embodying the knowledge management model. To reflect the content of the strategic model, a system is proposed: “the strategy concept-strategy”. The first one plays a pivotal role and implements a competence approach to the strategy, the second one fulfills the socio-economic tasks of the organization’s development. Each of them has its own goals and content. The strategy is formulated according to the unified scheme of strategic analysis under the conditions of soft management, which is associated with the regime called as “on the edge of chaos”.Conclusions. The mechanism is found which reflects the features of strategic management under the conditions of the knowledge economy. Further development of this methodology may consist of more detailed examination of the proposed methodology in the context of synergetic and fractal analysis.